2018
DOI: 10.1111/pops.12526
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Nature and Use of Promigrant Representations in an Antideportation Campaign

Abstract: Opposition to immigration and the rejection of migrants have long been of concern to psychologists. While much is known about negative representations of migrants in politics and the media, far less is known about positive representations of migrants and immigration. In this article, we provide an examination of social representations promoting promigrant action in the context of a community campaign opposing the deportation of a woman and her young daughter. The woman, who had come to the United Kingdom from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…Residents/nationals also used a ‘humanitarian frame’ to describe displaced people as a vulnerable group (Crawley, McMahon, & Jones, 2016). These findings are consistent with research that demonstrated how pro‐migrant discourse engages with problematic social representations to mobilize support for migrant rights (Ryan & Reicher, 2019). Nonetheless, the group’s activities seem to have dispelled, at least to some extent, anticipatory worries about how members of the groups see one another.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Residents/nationals also used a ‘humanitarian frame’ to describe displaced people as a vulnerable group (Crawley, McMahon, & Jones, 2016). These findings are consistent with research that demonstrated how pro‐migrant discourse engages with problematic social representations to mobilize support for migrant rights (Ryan & Reicher, 2019). Nonetheless, the group’s activities seem to have dispelled, at least to some extent, anticipatory worries about how members of the groups see one another.…”
Section: Discussionsupporting
confidence: 88%
“…These representations entrench negative stereotypes of displaced people, through their construction as a dehumanized ‘other’ (Breen, Haynes, & Devereux, 2006). To resist these representations, displaced people and their allies use discursive strategies such as invoking shared categories or emphasizing the benefits of solidarity over paternalism and charity (Ryan & Reicher, 2019; Wroe, 2018). Accordingly, ‘identities are always constructed through and against representations’ (Howarth, 2002, p. 20).…”
Section: Introductionmentioning
confidence: 99%
“…In general, prior research on leadership for social change and how leaders construct a group identity has focused on the rhetorical communication through top‐down process (leadership process through the leaders' rhetoric, for example, Reicher, Cassidy, Wolpert, Hopkins, & Levine, 2006; Ryan & Reicher, 2019, Selvanathan et al, 2019). The social identity approach of leadership is vital in understanding this process.…”
Section: Discussionmentioning
confidence: 99%